1984
DOI: 10.1128/aem.47.1.144-150.1984
|View full text |Cite
|
Sign up to set email alerts
|

Round robin investigation of methods for the recovery of poliovirus from drinking water

Abstract: Six laboratories actively involved in water virology research participated in a methods evaluation study, conducted under the auspices of the American Society for Testing and Materials Committee on Viruses in the Aquatic Environment, Task Force on Drinking Water. Each participant was asked to examine the Viradel (virus adsorption-elution) method with cartridge-type Filterite filters for virus adsorption and organic flocculation and aluminum hydroxide-hydroextraction for reconcentration. Virus was adsorbed to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

1984
1984
2014
2014

Publication Types

Select...
6
2
2

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(9 citation statements)
references
References 22 publications
3
6
0
Order By: Relevance
“…The high-pH glycine elution that had been the recommended procedure for eluting virus-laden cartridge filters (7,15,17) is no longer the method of choice. We subsequently found, as have others (10,14,16), that virus recovery was higher when beef extract was used as the eluent. Temperature was also a significant factor in virus recovery.…”
Section: Discussionsupporting
confidence: 71%
“…The high-pH glycine elution that had been the recommended procedure for eluting virus-laden cartridge filters (7,15,17) is no longer the method of choice. We subsequently found, as have others (10,14,16), that virus recovery was higher when beef extract was used as the eluent. Temperature was also a significant factor in virus recovery.…”
Section: Discussionsupporting
confidence: 71%
“…The virus titration experiments also indicated a possible source for some of the variable results obtained in our concentration experiments and in those reported by other laboratories (20). The coefficients of variation (standard deviation/mean) of the virus titers calculated from four experiments ranged from 0.02 to 0.31.…”
Section: Vol 52 1986supporting
confidence: 74%
“…Dahling and Wright (1984) reported that highest recoveries were obtained when 1600 mL of 3% beef extract was passed through the fi lters three times. This was also observed during round robin testing in which fi lters eluted with 3% beef extract yielded higher recoveries than those eluted with high-pH glycine (Melnick et al, 1984). Sobsey and Hickey (1985) used 0.3% beef extract in 50 mM glycine with one pass through the fi lter; Preston et al (1988) used 3% beef extract with 1 M sodium chloride to elute fi lters.…”
Section: Introductionmentioning
confidence: 73%